Immune (dys)regulation in multiple sclerosis: role of the CD95-CD95 ligand system - Zipp, Frauke; Krammer, Peter H.; Weller, Michael (Immunology today, 1999)
T cells specific for myelin antigens are thought to initiate and perpetuate the immune process behind multiple sclerosis. Apoptosis is a key regulatory mechanism that determines T-cell fate and might mediate tissue damage. Here, Frauke Zipp, Peter Krammer and Michael Weller discuss the role of the CD95-CD95 ligand system in multiple sclerosis.